Sanksi Pidana Terhadap Pencurian Ikan (Ilegal Fishing) di Laut Indonesia yang Dilakukan oleh Kapal Asing - I Nyoman Rama Cahyadi Putra; I Nyoman Gede Sugiartha; Luh Putu Suryani (Warmadewa Press, 2021)
Illegal fishing is fishing that is done illegally. The illegal domain is meant because it is contrary to the methods that have been prohibited in the law, both in terms of actions that can damage the sustainability of the fish ecosystem, which in this case is using fishing gear that can damage the condition of the aquatic ecosystem or fishing without having a fishing license which is also the realm of illegal fishing. In criminal acts, some acts are against criminal law. Criminal law is divided into two parts, namely objective criminal law and subjective criminal law. Sentencing is one of the efforts made by the state to change the behavior of a prisoner so that he can change and later return to society to become a better person. This study aimed to examine the regulation of illegal fishing carried out by foreign vessels in Indonesian seas and to reveal criminal sanctions against perpetrators of illegal fishing in the sea carried out by foreign vessels. This research was designed by using normative research with a statutory approach as well as a conceptual approach. The sources of legal materials consisted of primary and secondary legal materials. The collection of legal materials was done by collecting legal materials that were related to the material discussed. The technique of analyzing legal materials used a descriptive analysis system. Of the results of data analysis, it is discovered that fish theft occurs because of fishing without procedures that have been established in Indonesian waters and can be subject to sanctions in the form of imprisonment and fines.